2000
DOI: 10.1212/wnl.54.5.1064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of RLS in an elderly population

Abstract: RLS is a frequent syndrome in the elderly with considerable impact on self-perceived mental health, affecting women about twice as often as men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
361
3
39

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(445 citation statements)
references
References 15 publications
39
361
3
39
Order By: Relevance
“…Regarding the male population, the prevalence of RLS was 5.76%. This rate is similar to the one shown by Rothdach 4 and Ulfberg 23 . The latter author conducted a study with an exclusively male population and the prevalence of RLS was 5.8%.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the male population, the prevalence of RLS was 5.76%. This rate is similar to the one shown by Rothdach 4 and Ulfberg 23 . The latter author conducted a study with an exclusively male population and the prevalence of RLS was 5.8%.…”
Section: Resultssupporting
confidence: 90%
“…Fifty years after its complete description, definition and major criteria to its diagnosis was published by a group entitled International Restless Legs Syndrome Study Group (IRLSSG) 2 . Despite the fact of being long known and of high prevalence in the population, knowledge about RLS still remains very limited among health care professionals 3,4 .…”
mentioning
confidence: 99%
“…Previous population-based studies found an increasing prevalence of RLS with age 11 , and controversial results about gender 11,13 . Unlike primary RLS, it seems that age and gender are not important factors for the development of RLS in CRF subjects.…”
Section: Discussionmentioning
confidence: 92%
“…Data in population-based studies 11,13 about correlation between RLS and smoking was controversial. Many of our patients might have felt ashamed or frightened when asked about smoking habits, so we cannot attest the reliability of our results.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similarly, hormone replacement therapy use was found to be significantly more frequent in women with RLS in one study 15 but not in two others. 16,17 In a randomized study of hormonal therapy for postmenopausal women, RLS complaints were significantly less for those on estrogen + progesterone compared to baseline, but not different for those on estrogen or progesterone alone. 18 Perhaps there is a genetically predisposed subset of women for whom estrogen is an exacerbating factor, but this relationship may be diminished when all women are considered.…”
Section: Disclosure Statementmentioning
confidence: 99%